Changing practice: the possibilities and limits for reshaping social work practice - Laird, Siobhan E.; Morris, Kate; Archard, Philip; Clawson, Rachael (SAGE Publications, 2017)
Since 2010 the United Kingdom has witnessed a number of initiatives that shift away from reliance on performance management to improve social work with children and families, towards a renewed interest in practice models. This study reports on the evaluation of a local government programme in England to introduce and embed systemic family practice through the roll out of intensive training to social workers and frontline managers. It was anticipated through the programme that child protection social workers would undertake more direct work with families and build more positive relationships, resulting in a fall in the number of child protection plans and children experiencing repeat periods of care. The evaluation adopted a mixed method approach encompassing an online survey of social workers, interviews with team managers and family members, a case audit and statistical analysis of local level metrics. It found limited employment of systemic family practice or improvement due to the programme. Adopting the 7 S framework, this study examines the barriers to and facilitators of successful change and identifies generic considerations for change programmes in child protection social work.